Determination of a new uniform thorax density representative of the living population from 3D external body shape modeling. Issue 7 (3rd May 2016) - Amabile, Celia; Choisne, Julie; Nérot, Agathe; Pillet, Hélène; Skalli, Wafa
Abstract: Body segment parameters (BSP) for each body׳s segment are needed for biomechanical analysis. To provide population-specific BSP, precise estimation of body׳s segments volume and density are needed. Widely used uniform densities, provided by cadavers׳ studies, did not consider the air present in the lungs when determining the thorax density. The purpose of this study was to propose a new uniform thorax density representative of the living population from 3D external body shape modeling. Bi-planar X-ray radiographies were acquired on 58 participants allowing 3D reconstructions of the spine, rib cage and human body shape. Three methods of computing the thorax mass were compared for 48 subjects: (1) the Dempster Uniform Density Method, currently in use for BSPs calculation, using Dempster density data, (2) the Personalized Method using full-description of the thorax based on 3D reconstruction of the rib cage and spine and (3) the Improved Uniform Density Method using a uniform thorax density resulting from the Personalized Method. For 10 participants, comparison was made between the body mass obtained from a force-plate and the body mass computed with each of the three methods. The Dempster Uniform Density Method presented a mean error of 4.8% in the total body mass compared to the force-plate vs 0.2% for the Personalized Method and 0.4% for the Improved Uniform Density Method. The adjusted thorax density found from the 3D reconstruction was 0.74 g/cm 3 for men and 0.73 g/cm 3 for women instead of the one provided by Dempster (0.92 g/cm 3 ), leading to a better estimate of the thorax mass and body mass.